Atributos de influência na escolha do ponto de venda para os consumidores do pequeno varejo de materiais para construção - Lima, Alan Souza (2016)
The objective of this research was analyse the influence of the attributes of small shops on the building sector that are considered important to the consumer decid in what store will buy the products, by the identification of the most important factors that are decisive on your own choice, althoug this study demonstrated the wishes of these customers, and was presented thus a note about the relation price x perceived quality. The study described another researches, not only on retail building materials, but thus on other reatil segments, and was demonstrated the results of theses investigations. The methodology applied was quantitative, conclusive and descriptive, done by the active clientes of a small store building materials who responded the questions using a Likert 5-point scale. Where used the software Microsoft Excel® 2013, and the software IBM SPSS Statistics, 24. For the interpretation of these data was adopted the Cronbach alpha, the Peasron’s correlation coefficient, and thus the One-Way Anova. The data indicated that the main attibute for these consumers is the variety and avaiability of products, followed by fast service and cuts. This way, the study demonstrated that the analysis of the preferences of consumers of building materials can not be only summarized by the strategy of low price, but too understand the customer needs using all attributes related to satisfaction of consumers in general